2013
DOI: 10.1186/1471-2334-13-203
|View full text |Cite
|
Sign up to set email alerts
|

Plasma metabolomics identifies lipid abnormalities linked to markers of inflammation, microbial translocation, and hepatic function in HIV patients receiving protease inhibitors

Abstract: BackgroundMetabolic abnormalities are common in HIV-infected individuals on antiretroviral therapy (ART), but the biochemical details and underlying mechanisms of these disorders have not been defined.MethodsUntargeted metabolomic profiling of plasma was performed for 32 HIV patients with low nadir CD4 counts (<300 cells/ul) on protease inhibitor (PI)-based ART and 20 healthy controls using liquid or gas chromatography and mass spectrometry. Effects of Hepatitis C (HCV) co-infection and relationships between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
120
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 95 publications
(103 reference statements)
10
120
2
2
Order By: Relevance
“…Decreases observed in levels of -6 PUFAs and lysolipids from infected blood during 3 dpi suggests that both arms of AA production were disrupted. These results are consistent with other metabolomics studies of infection whose results have indicated the importance of eicosanoids and lysolipids during infection (45,50,63). However, it appears that decreases in levels of eicosanoids and lysolipids are not universal traits during bacterial infections.…”
Section: Discussionsupporting
confidence: 82%
“…Decreases observed in levels of -6 PUFAs and lysolipids from infected blood during 3 dpi suggests that both arms of AA production were disrupted. These results are consistent with other metabolomics studies of infection whose results have indicated the importance of eicosanoids and lysolipids during infection (45,50,63). However, it appears that decreases in levels of eicosanoids and lysolipids are not universal traits during bacterial infections.…”
Section: Discussionsupporting
confidence: 82%
“…30 There is in vitro and clinical evidence that PIs can cause mitochondrial dysfunction through the generation of reactive oxygen species and by triggering pathways of mitophagy. 31,32 Importantly, PIs can also cause insulin resistance. FAO is perturbed in patients with insulin resistance, resulting in abnormal acylcarnitine levels 33 and excessive acylcarnitines may even play a role in the signaling pathways that lead to the development of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolite extraction was performed as previously described (Evans et al, 2009). Metabolite extracts were subjected to three analyses: gas chromatography and mass spectrometry, ultra HPLC and tandem mass spectrometry optimized for basic metabolites, and ultra HPLC and tandem mass spectrometry optimized for acidic metabolites (Cassol et al, 2013). Relative abundance was determined for 194 identified (named) metabolites.…”
Section: Metabolite Profilingmentioning
confidence: 99%